(untitled) (Scientific journal of the Fergana State University, 2024)
The butterfly Arctia caja, belonging to the family Eribidae, was first recorded in the southern territories of the Fergana Valley. Arctia caja is considered a univoltine species, develops in one generation, and its butterflies fly in June-July. The active period of the larvae is August-October and May-June. Damages leaves of Rubus idaeus, Rubus fruticosus, Malus, Pyrus, Prunus domestica, Fragaria, Crataegus, Populus, Salix. According to food specialization, it is a broad polyphagous, summer species belonging to the mesophilic ecological group. They overwinter in the larval stage from the second half of the autumn season. As a result of the research, data on biology, distribution, harmfulness and morphological description of Arctia caja in the southern territories of the Fergana Valley are provided.